Study On Different Parameters Of An Inertia-Type Piezoelectric Actuator In Reducing The Vibration Of Suspended Handle Model - Abdul Razak, Mohamad Noorhazim (Universiti Sains Malaysia, 2022)
Currently, the dependency on the use of handheld power tools such as jack hammer and pneumatic grinder among the industry workers are substantially high due to its wide functionality and great efficiency which make the performed tasks become easier. Nevertheless, these tools are subjected to the undesirable vibration during operation which may cause adverse effects to workers’ health after a long exposure such as the development of HAVs. In the published literature, there are very limited simulation studies on vibration attenuation of suspended handle using an inertia-type piezoelectric actuator, whereby a wide range of parametric study can be done to investigate the performance of the piezoelectric actuator. Therefore, this research will investigate different parameters of an inertia-type piezoelectric actuator in reducing the vibration of suspended handle model using simulation in MATLAB and Simulink software. From the result, AVC system with ZN tuning method is the most effective in reducing the vibration of suspended handle compared to PID (auto and manual) and passive system. Among the tuning parameters, ZN method with the tuned parameter of 10 times higher than original value has the best performance with 99.96% vibration attenuation of suspended handle. As a conclusion, the AVC system with ZN tuning method is a promising solution for the vibration control, particularly in the application of power tools.